Analysis of thermo acoustic stack geometry - Mohd. Ghazali, Normah (Penerbit UTM, 2008)
Increasing awareness on sustainability of energy resources since the Brundtland Report (Brundtland report) has spurred much research into alternative energy technologies across the globe. The Malaysian government, without exception, through government research bodies and public universities has continued its encouragement towards the exploration of sustainable production, processing, and utilization of its resources. Thermo acoustics technology, currently viewed as a potential replacement for the conventional refrigeration systems is one of the research area being pursued. With almost no moving parts, no hazardous refrigerants, and considered as “low technology” with no critical dimensions, a thermo acoustic cooling system may indeed be the answer to the ecological threat posed by the production of harmful refrigerants that is related to global warming and the thinning of the ozone layer. Thermo acoustics theory is a field associated with either a temperature gradient induced by oscillations, or oscillations induced by a temperature gradient. The former is an everyday event with negligible temperature gradients of the order ~10 -4 °C produced by sound waves. The latter was probably first observed by European glass blowers over 200 years ago when sound was sometimes heard when a hot glass bulb was attached to a cooler glass tube. The practical usefulness of the phenomenon, however, has only been realized in the late eighties with the first cryocooler probably made by Hofler in 1985 (Hofler, 1986). The last twenty years have seen fast developments in research into the thermo acoustics effects and systems. Theoretical and experimental works are many in developed countries with numerical studies slowly catching up due much to the nonlinearities and multidimensional effects that have to be addressed. NASA and the Los Alamos National Laboratory (LANL) USA had successfully developed a high efficiency power source based on thermo acoustic technology, while Ben and Jerry in collaboration with Penn State University in USA developed an ice cream refrigerator with 120 Watt power (Garret et al.1993 and www.benjerry.com) . The stack of the thermo acoustic system is considered as the heart of a thermo acoustic system. Development and continuous improvement of it can thus lead to a better overall performance of a thermo acoustic system. The heat transfer process crucial to thermo acoustic effects occurs in and near the stack region and current technology of the stack material and geometry has room for improvement based on the background completed. Figure 7.1 shows the stack’s position within a simple cylindrical resonator and the associated temperature difference, ?T, across the stack that developed as a result of compression and expansion of the fluid particles generated by a speaker/driver. Various researchers have recommended various stack gaps using latest discovery of the best performance stack material (i.e. Mylar). Theoretical analysis has shown that a pin-array stack performed better than a parallel plate stack but the spiral roll stack, however, is probably the easiest to be fabricated. Universiti Teknologi Malaysia (UTM) through research grants from the Ministry of Science and Technology (MOSTI) has been involved in thermo acoustic research since 2002. This chater reports the study of the thermo acoustic effects with a stack geometry fabricated from paper. Variation of parameters such as the stack thickness and separation gap and their effects on the temperature difference across the stack are investigated.